สิทธิ สวัสดิการและการปรับตัวของผู้พิการทางสายตา - จันทิมา เจริญสุภกร (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
To study family background, education, environment, and self adjustment of people with visual disability, which are conditioned by the complicate economics, social, and political situations.The rights and welfare of the state and private organizations also affect the chance to reach those people. This research selects 5 cases with visual disability from the Skills Development Center for the Blind at Nonthaburi Province, and another 5 cases from the Foundation for the Employment Promotion of the Blind. The qualitative research method was employed. The research finds that family background, environment, deformation conditions,rights and welfare, and self adjustment of case studies from both places are similar. There is only some difference in education and work skill of the disabled. The Foundation for the Employment Promotion of the Blind allows people with visual disability to study at the Department of Non-Formal Education while attending training for occupations. However, the Skills Development Center for the Blind at Nonthaburi Province does not. It offers working training in various occupations such as weaving reed mat and farm work. While the Foundation for the Employment Promotion of the Blind offers only training in Thai traditional massage. Finally, all case studies can adjust themselves to their daily life activities.